Wernicke`s encephalopathy manifesting with diplopia after ileojejunostomy: report of a pediatric case with Hirschsprung disease - Dilber, Beril; Kamaşak, Tülay; Eyüboğlu, İlker and Kola, Mehmet and Uysal, Ahmet Taner and Saruhan, Haluk and Yalçın, Sonay and Sağ, Elif and Cansu, Ali (The Turkish Journal of Pediatrics, 2020)
Background. Wernicke`s encephalopathy (WE) is a coenzyme-induced disease with acute neuropsychiatric symptoms leading to high mortality and morbidity due to thiamine deficiency. WE is mostly caused by alcoholism in adult populations; however, it is often associated with gastrointestinal surgical procedures, recurrent vomiting, chronic diarrhea, cancer and chemotherapy treatment, systemic diseases, drugs, magnesium deficiency, and malnutrition in children. Although these predisposing factors are considered to be uncommon in children, they are actually highly frequent and can be fatal if not treated promptly. Case. In this report, we present a patient who developed diplopia during total parenteral nutrition following surgical resection and was diagnosed with WE. The findings of the patient’s cranial magnetic resonance imaging (MRI) findings were consistent with those of WE and the ocular findings of the patient resolved completely after thiamine treatment. Conclusion. Although WE is rare in children it can be prevented by early diagnosis and treatment and oculomotor findings such as diplopia can be a warning sign.